1994
DOI: 10.1111/j.1349-7006.1994.tb02966.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of Intestinal‐type Alkaline Phosphatase in Stomach Tumors Induced by N‐Methyl‐N′‐nitro‐N‐nitrosoguanidine in Rats

Abstract: A potyclonal antibody against rat intestinal‐type alkaline phosphatase (I‐ALP) was generated and proven to be applicable immunohistochemically to paraffin‐embedded sections. Expression of I‐ALP in normal tissues, intestinal metaplasia and stomach tumors induced by N‐methyl‐N′‐nitro‐N‐nitroso‐guanidine (MNNG) was then investigated in five different strains of rats. Male SD (Crj:CD), Lewis (LEW/Crj), WKY (WKY/NCrj), Wistar (CrjrWistar) and F344 (F344/DuCrj) animals were given drinking water containing 100/μ/ml o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…[29][30][31][32][33] By sequential observation of rat glandular stomach carcinomas and comparisons of phenotypic expression of human gastric carcinoma cells between early and advanced cases, a phenotypic shift from gastric to intestinal epithelial cell type expression has been recognized with progression of each histological type of gastric carcinomas. [33][34][35][36] The present results regarding phenotypic expression of tumor cells showed that mouse glandular stomach adenomas and carcinomas consist solely of tumor cells of gastric epithelial cell type, without any intestinal metaplasia in the mucosa surrounding carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] By sequential observation of rat glandular stomach carcinomas and comparisons of phenotypic expression of human gastric carcinoma cells between early and advanced cases, a phenotypic shift from gastric to intestinal epithelial cell type expression has been recognized with progression of each histological type of gastric carcinomas. [33][34][35][36] The present results regarding phenotypic expression of tumor cells showed that mouse glandular stomach adenomas and carcinomas consist solely of tumor cells of gastric epithelial cell type, without any intestinal metaplasia in the mucosa surrounding carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…We have proposed [27][28][29][30][31] that, in humans, intestinal metaplasia and the appearance of the intestinal epithelial cell phenotype in gastric carcinomas during carcinogenesis are independent phenomena, although it had earlier been suggested 9) that the intestinal-type carcinomas might develop from intestinal metaplasia and that diffuse-type carcinomas might originate from nonmetaplastic mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…(Received July 22, 1997/Revised October 6, 1997 Revised November 27, 1997/Accepted November 27, 1997) …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Anti-rat Pg1 20 and anti-rat I-ALP antibodies were prepared 16 for immunohistochemical analyses. The avidinbiotin complex method with a Vectastain ABC kit (Vector Laboratories Inc., Burlingame, CA) was used for detection.…”
Section: Immunohistochemical Enzyme Histochemical and Mucin Histochementioning
confidence: 99%
“…However, there are differences with regard to intestinal change in the stomach between the human and mouse cases. We have examined carcinogenesis with MNU in six strains of mice (BALB/cA, C57BL/6N, CBA/JN, C3H/HeN, DBA/2N, and CD-1) and the typical intestinal metaplasia and intestinal type gastric tumors which appear in the rat 15,16 were not observed, despite the fact that the lesions positive for intestinal alkaline phosphatase (I-ALP), a marker of intestinal absorptive cells, could be detected with immuno-and enzyme-techniques 17 . Since intestinal metaplasia is commonly observed in the human stomach of old individuals, it could be considered as an age-related change.…”
Section: Introductionmentioning
confidence: 99%